For God did not so love the whole world – only Israel! John 3:16 revisited - Botha, J. E. (HTS teologiese studies, 2005)
John 3:16 is probably the most popular and widely proclaimed proof-text for God’s love for all of humankind – the “world”. This interpretation of the verse is based on a meaning for which the Greek word cosmos can be used, but the word is used to denote many other meanings as well. The one interpretation of cosmos as “world” is then read into all instances where cosmos appears, including John 3:16. This position is held and defended by some in an almost fanatical manner by some. However, if this verse is exegetically considered in its primary context, the Fourth Gospel, it becomes clear that John 3:16 does not speak of God’s universal love of all of human kind. Far from it. The verse indeed has a completely different meaning.